Housing policy and housing finance in the Czech republik during transition - Lux, Martin (IOS Press, 2013)
This book contains the description and evaluation of a profound housing system reform constituting part of the transition from a centrally planned to a market economy in the Czech Republic. It addresses two goals: to evaluate housing subsidies (reforms) by application of improved methods of welfare economics and, secondly, to list the main factors explaining the particular outcomes of selected reforms. The author applied methods of welfare economics for an evaluation of housing subsidies in a scale unique in housing studies. The analysis of underlying factors influencing formation of housing reforms brought new findings about the essence of transition in post-socialist countries